2006
DOI: 10.1136/bjsm.2006.029769
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tendinopathy: effectiveness of eccentric exercise

Abstract: This review demonstrates the dearth of high-quality research in support of the clinical effectiveness of EE over other treatments in the management of tendinopathies. Further adequately powered studies that include appropriate randomisation procedures, standardised outcome measures and long-term follow-up are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(156 citation statements)
references
References 70 publications
1
146
2
7
Order By: Relevance
“…These oscillations may modulate the therapeutic effects attributed to eccentric exercise regimen 116 . While many have advocated eccentric exercise programs, others have suggested that understanding the mechanisms involved in these regimens is necessary to support the efficacy of these programs for treatment 117,118 . The optimal load, speed of movement, number of repetitions, and duration of contraction remain to be determined and require further investigation 109,116 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…These oscillations may modulate the therapeutic effects attributed to eccentric exercise regimen 116 . While many have advocated eccentric exercise programs, others have suggested that understanding the mechanisms involved in these regimens is necessary to support the efficacy of these programs for treatment 117,118 . The optimal load, speed of movement, number of repetitions, and duration of contraction remain to be determined and require further investigation 109,116 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Eccentric exercise therapy has been reported to have some effect in prospective, randomized trials in athletic patients; 54,55 however, a review of 20 published trials found that there was little evidence of a positive effect on clinical outcomes, such as reduction of pain, return to function and patient satisfaction. 56 Shock-wave therapy, which is thought to function on the tenocytes to stimulate repair, might be effective in a carefully selected group of patients, 57 although other studies have reported no significant effect. 58,59 Growth factors have been used for several years in an attempt to improve tendon healing, but there is currently no evidence that these are effective in tendinopathies.…”
Section: New Treatments For Tendinopathy and Future Research Directionsmentioning
confidence: 99%
“…A review of conservative treatment outcomes for tendinopathy at multiple common sites other than the biceps compared the use of an eccentric exercise programs to control groups including concentric exercise, stretching, splinting, massage, and ultrasound. The review suggests that eccentric exercise may decrease pain at twelve weeks of physical therapy versus twelve weeks of concentric exercise [59]. In cases where conservative treatment fails, patients may undergo surgical intervention consisting of either a biceps tenotomy or tenodesis depending on multiple factors including associated pathology, age, hand dominance, and activity level.…”
Section: Treatmentmentioning
confidence: 99%